Antiosteoporosis effect of tanshinol in osteoporosis animal models: A systematic review and meta-analysis - Wang, Shen; Yuan, Yifeng; Lin, Qian; Zhou, Hang; Tang, Binbin; Liu, Yang; Huang, Hai; Liang, Bocheng; Mao, Yingdelong; Liu, Kang; Shi, Xiaolin (Frontiers in Pharmacology, 2022)
Background: Osteoporosis (OP) is an age-related bone disease that has emerged as a worldwide public health concern due to its increasing incidence and high disability rate. Tanshinol [D (+) β-3,4-dihydroxyphenyl lactic acid, TS], a water-soluble component extracted from Salvia miltiorrhiza, has proven to be effective in attenuating OP in vitro and in vivo. However, there is insufficient evidence to support its clinical application. Objective: This meta-analysis aimed to investigate available OP animal model studies to demonstrate the antiosteoporosis effects of TS in a systematic manner. Methods: Electronic searches of related studies were conducted in the following databases: EMBASE, PubMed, Web of Science, Cochrane Library, Chinese National Knowledge Infrastructure, Chinese VIP Database, Chinese Biomedical Literature Database, and Wanfang. The retrieval date was January 2022, and there were no time or language restrictions. The CAMARADES 10-item quality checklist was utilized to test the risk of potential bias for each study, and modifications were performed accordingly. The primary outcome was bone mineral density (BMD, which included the femur and lumbar spine); and secondary outcomes were parameters for trabecular bone such as bone volume over total volume (BV/TV), trabecular number (Tb.N), trabecular thickness (Tb.Th), trabecular separation (Tb.Sp), conditions of the femur (including bone maximum load and bone elastic load), and markers of bone metabolism (serum osteocalcin, S-OCN). Results: A total of nine studies including 176 rats were chosen for this analysis. Egger’s test revealed the presence of publication bias in various studies regarding the primary outcome. According to this systematic review, TS significantly increased the BMD of the femur (BMD-femur) (SMD = 4.40; 95% CI = 1.61 to 7.19; p = 0.002, I2 = 94.6%), BMD of the lumbar spine (BMD-lumbar) (SMD = 6.390; 95% CI = 2.036 to 10.744; p = 0.004, I2 = 95.9%), BV/TV (SMD = 0.790; 95% CI = 0.376 to 1.204; p = 0.000, I2 = 10.8), Tb.N (SMD = 0.690; 95% CI = 0.309 to 1.071; p = 0.000, I2 = 12%), Tb.Th (SMD = 0.772; 95% CI = 0.410 to 1.134; p = 0.000, I2 = 32.2%), and S-OCN (SMD = 3.13; 95% CI = 0.617 to 5.65; p = 0.015, I2 = 92.3%), while the Tb.Sp level was markedly decreased in OP models in comparison to the controls (SMD = −0.822; 95% CI = −1.207 to −0.437; p = 0.000, I2 = 0%). Moreover, TS treatment was associated with a significant improvement of the bone biomechanical indicators, including bone maximum load (SMD = 0.912; 95% CI = 0.370 to 1.455; p = 0.001, I2 = 40%) and elasticity load (SMD = 0.821; 95% CI = 0.290 to 1.351; p = 0.002, I2 = 0%). Conclusion: Collectively, our findings suggest that TS can improve BMD, bone microarchitecture, bone biomechanics, and S-OCN expression in rats, implying that it could be used clinically in the future. Systematic Review Registration:https://inplasy.com/inplasy-2022-3-0053/, identifier [INPLASY202230053].